Impact of Annexin A 7 Deficiency on FGF23 Plasma Concentrations - Anja T. Umbach; Omar El-Attar; Dong Luo; Hajar Fakhri; Rosi Bissinger; Florian Lang (Karger Publishers, 2016)
Background/Aims: The release of fibroblast growth factor FGF23, a powerful regulator of 1,25(OH)2D3 formation and mineral metabolism, is stimulated by store-operated Ca2+ entry (SOCE), which is accomplished by the pore forming Ca2+ release activated channel protein Orai1. Regulators of Orai1 and thus FGF23 release include serum & glucocorticoid inducible kinase SGK1, a kinase up-regulated by glucocorticosteroids. Some effects of glucocorticoids require the presence of annexin A7, such as suppression of prostaglandin E2 in gastric glands. The present study thus explored whether annexin A7 impacts on FGF23 plasma levels. Methods: Comparisons were made between gene targeted mice lacking functional annexin A7 (Anx7-/-) and their wild type littermates (Anx7+/+). Serum C-terminal-FGF23, intact FGF23, 1,25(OH)2D3 and PTH concentrations were measured by ELISA or EIA. The serum and urinary phosphate concentrations were measured by colorimetry, the serum Ca2+ concentration and the urinary Ca2+ concentration by flame photometry. Results: Serum C-terminal FGF23 levels and corticosterone levels were significantly higher and serum 1,25(OH)2 D3 and PTH levels were significantly lower in Anx7-/- than in Anx7+/+ mice. Water intake was slightly but significantly higher in Anx7-/- mice than in Anx7+/+ mice. No significant difference was observed between Anx7-/- and Anx7+/+ mice in urinary fluid excretion, plasma Ca2+ concentration, plasma phosphate concentration and urinary Ca2+ output. The urinary phosphate output was significantly lower in Anx7-/- mice than in Anx7+/+ mice. Conclusion: Annexin A7 deficiency upregulates FGF23 plasma levels, an effect paralleled by increased corticosterone plasma levels, as well as decreased 1,25(OH)2 D3 and PTH plasma levels.